(untitled) (Research, Society and Development, 2023)
This literature review addresses monkeypox, an infectious disease caused by the Monkeypox virus that belongs to the genus Orthopoxvirus and to the family Poxviridae, the same as the human smallpox virus. It had its first case registered in Congo in 1970. After almost 40 years, with no reported case, in 2017 it re-emerged in Nigeria. With the absence of mass vaccination and its transmission occurring through direct contact with people infected through close and prolonged exposure to droplets or other respiratory secretions, this virus has already originated in more than 44 countries, causing a new global pandemic. With a low mortality rate, which can reach between 3% and 6%, its symptoms are very similar to those observed in patients with smallpox, although they are clinically less severe. Thus, the present work aimed to study the characteristics and general aspects of monkeypox, in order to take measures to prevent and promote this disease.